Early administration of imatinib mesylate reduces plexiform neurofibroma tumor burden with durable results after drug discontinuation in a mouse model of neurofibromatosis type 1. Issue 8 (27th May 2020) - Armstrong, Amy E.; Rhodes, Steven D.; Smith, Abbi; Chen, Shi; Bessler, Waylan; Ferguson, Michael J.; Jiang, Li; Li, Xiaohong; Yuan, Jin; Yang, Xianlin; Yang, Feng‐Chun; Robertson, Kent A.; et al.
Abstract: Background: Neurofibromatosis type 1 (NF1) is a common genetic disorder characterized by plexiform neurofibromas (pNF), which are thought to be congenital tumors that arise in utero and enlarge throughout life. Genetic studies in murine models delineated an indispensable role for the stem cell factor (SCF)/c‐kit pathway in pNF initiation and progression. A subsequent phase 2 clinical trial using imatinib mesylate to inhibit SCF/c‐kit demonstrated tumor shrinkage in a subset of preexisting pNF; however, imatinib's role on preventing pNF development has yet to be explored. Procedure: We evaluated the effect of imatinib dosed at 10‐100 mg/kg/day for 12 weeks to one‐month‐old Nf1 flox/flox ;PostnCre(+) mice, prior to onset of pNF formation. To determine durability of response, we then monitored for pNF growth at later time points, comparing imatinib‐ with vehicle‐treated mice. We assessed gross and histopathological analysis of tumor burden. Results: Imatinib administered preventatively led to a significant decrease in pNF number, even at doses as low as 10 mg/kg/day. Tumor development continued to be significantly inhibited after cessation of imatinib dosed at 50 and 100 mg/kg/day. In the cohort of treated mice that underwent prolonged follow‐up, the size of residual tumors was significantly reduced as compared with age‐matched littermates that received vehicle control. Conclusions: Early administration of imatinib inhibits pNF genesis in vivo, and effects are sustained after discontinuation of therapy. These findings may guide clinical use of imatinib in young NF1 patients prior to the substantial development of pNF.